2002
DOI: 10.1207/s15327655jchn1904_03
|View full text |Cite
|
Sign up to set email alerts
|

Challenges in Home Care Practice: A Decision-Making Perspective

Abstract: A qualitative approach using an ethnographic design was used to investigate the nature of clinical decision making in home care practice from home care nurses' perspective. In-depth interviews were conducted with experienced home care nurses (N = 16) in addition to observations of nurses during meetings and client visits. The findings indicate that the decision-making challenges involved in home care practice consisted of the following 4 major categories: (a) challenges that arise in the development of client-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
50
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(51 citation statements)
references
References 15 publications
1
50
0
Order By: Relevance
“…Moreover, there exist a number of concerns in providing nursing care for home care patients such as a lack of ability to track patient's health and hospitalization history, a lack of readily available knowledge in specialty areas, a disconnect in communication among nurse team members, other disciplines, and patients, and a limited amount of time to provide complex patient care [26, 35, 42]. These problems related to inadequacies in information access and communication, make it more difficult for the nurses to make appropriate clinical decisions, and can lead to frustration or lack of control for nurses [26].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, there exist a number of concerns in providing nursing care for home care patients such as a lack of ability to track patient's health and hospitalization history, a lack of readily available knowledge in specialty areas, a disconnect in communication among nurse team members, other disciplines, and patients, and a limited amount of time to provide complex patient care [26, 35, 42]. These problems related to inadequacies in information access and communication, make it more difficult for the nurses to make appropriate clinical decisions, and can lead to frustration or lack of control for nurses [26].…”
Section: Introductionmentioning
confidence: 99%
“…These problems related to inadequacies in information access and communication, make it more difficult for the nurses to make appropriate clinical decisions, and can lead to frustration or lack of control for nurses [26]. …”
Section: Introductionmentioning
confidence: 99%
“…Three studies used member checking as a way to strengthen the validity of the analysis (Smith Higuchi et al . , Johansson et al . , Arbon et al .…”
Section: Resultsmentioning
confidence: 99%
“…Five of the included studies reported the need for increased knowledge of how to overcome challenges such as problems associated with communication and/or collaboration as a leader and manager in the care of older persons (Smith Higuchi et al . , Henriksen & Rosenqvist , Ross et al . , Arbon et al .…”
Section: Resultsmentioning
confidence: 99%
“…Nurses routinely use these interrelated patterns of reasoning to make decisions that influence patient care and outcomes (Tanner, 2006). Previous research highlights the importance of knowing the patient and family in order to make appropriate clinical decisions (Egan et al, 2009; Smith Higuchi, Christensen, & Terpstra, 2002; Stajduhar et al, 2011). Decision-making also relies on personal values and professional scope of practice (Gillespie & Paterson, 2009), as well as prior experiences with similar situations, which facilitates the evaluation and weighing of potential decisional alternatives (Tversky & Kahneman, 1974).…”
Section: Introductionmentioning
confidence: 99%